2022
DOI: 10.1212/wnl.0000000000200029
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy vs Bridging Therapy for Anterior Circulation Large Vessel Occlusion Stroke

Abstract: Backgroundand Purpose: Current guidelines recommend the use of mechanical thrombectomy (MT) plus intravenous thrombolysis (aka bridging therapy, [BT]) for patients with anterior circulation large vessel occlusion (LVO) stroke. However, clinical equipoise exists in relation to the use of BT versus MT alone. Our objective is to compare the efficacy and safety of BT to MT for anterior circulation LVO.Methods:A systematic search of biomedical literature databases was performed from inception to October 29, 2021 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 37 publications
(53 reference statements)
0
37
0
Order By: Relevance
“…The PRISMA flow diagram of search strategy and the process of screening and study selection are shown in figure 1. Twenty-five relevant studies were finally included in qualitative synthesis 15–20 24–42…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PRISMA flow diagram of search strategy and the process of screening and study selection are shown in figure 1. Twenty-five relevant studies were finally included in qualitative synthesis 15–20 24–42…”
Section: Resultsmentioning
confidence: 99%
“…Two studies used the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) for quality assessment 30 37. In accordance with AMSTAR-2, 17 studies were rated ‘high’, and nine were rated ‘moderate’.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MT may be superior to IVT for AIS caused by embolization of a myxoma fragment. However, IVT is still recommended as first-line treatment of AIS based on recent RCT evidence demonstrating that BT offers more benefits than MT alone for functional outcomes and recanalization rates without compromising safety ( 37 ). Thus, for now, IVT should not be withheld in CM-AIS patients with LVOs.…”
Section: Discussionmentioning
confidence: 99%
“…38 In addition, several observational studies have previously addressed the additional benefit of IVT before MT in AIS-LVO with varying results. 38–40…”
Section: Thrombolysis Bridge Is Down?mentioning
confidence: 99%